Characterization of Glutamatergic Phenotypes in Hybrid Septal Neuroblastoma (SN56) cells - Pacheco, Luis F (2014)
Septal Neuroblastoma (SN 56) cells are hybrid cells made through cell fusions between quiescent medial septum neurons (cholinergic) and tumoral neuroblastoma cells. Cholinergic cells synthesize and release the neurotransmitter acetylcholine. Preliminary studies in our laboratory revealed that SN 56 neurons also express the vesicular glutamate transporter type 1 (VGluT1), a protein that is normally produced by glutamatergic neurons. This discovery prompted us to hypothesize that SN 56 neurons may also co-express a glutamatergic phenotype which is important because glutamatergic neurons have been associated to the pathogenesis of neurological disorders such as Alzheimer’s disease. To assess whether SN 56 neurons express in fact both phenotypes, we conducted experiments in differentiated and no differentiated SN 56 cell, to confirm the expression of glutamatergic phenotype, by qPCR, western blotting and Immunocytochemistry assay. The cells are cultured in an incubator gassed with 5% CO2 at 37°C. After differentiation for 3-5 days with cAMP and retinoic acid, SN 56 cells were prepared for qPCR, western blotting and immunocytochemistry. Cells were separated by each experiment, primary antibodies or primers against NMDA glutamate receptor subunit NR2B, VG luT1 and vesicular cholinergic transport (ChAT) how positive control were used to confirm our hypothesis,. Expression of these markers will indicate a glutamatergic phenotype. After secondary detection with appropriate fluorescently-labeled antibodies we confirmed that differentiated SN 56 neurons express glutamate NR2B receptor subtype and the VGluT1 transporter in both post-synaptic and presynaptic structures respectively. Hence, these findings support our hypothesis that SN 56 neurons can co-express both cholinergic and glutamatergic phenotype.